Analysis of Root System Architecture Affected by Swarming Behavior - Li, Songyang; Yu, Wenqi; Liu, Xiaodong; Wang, Miao (Journal of Horticultural Research, 2020)
The root system architecture (RSA) displays complex morphological characteristics because of diverse root growth behaviors. Recent studies have revealed that swarming behavior among roots is particularly important for RSA to adapt to environmental stimuli. However, few models are proposed to simulate RSA based on swarming behavior of roots. To analyze plasticity of RSA affected by swarming behavior, we propose viewing it as a swarm of single roots. A swarming behavior model is proposed by considering repulsion, alignment, and preference of individual single roots. Then, the swarming behavior model is integrated into a simple and generic RSA model (called ArchiSimple). Lastly, characteristics of RSA affected by swarming behavior model and non-swarming behavior model are compared and analyzed under three different virtual soil sets. The characteristics of RSA (such as primary root length, lateral root length, lateral roots, and resource uptake) are significantly promoted by swarming behavior. Root system distributions can also be greatly affected by swarming behavior. These results show that root foraging and exploration in soil can be regarded as collective behavior of individual single root.